Estudio Criminológico Comparado del Delito de Femicidio en el Derecho Penal - Rojas Rojas, Deicy Gabriela (2019)
Thepresent work of legal research is entitled: "Comparative Criminology Study of Crime of Femicide in Criminal Law", it is observed that women during development and social change have been marginalized, discriminated and mistreated, both in the family, private and public; what made it necessary for them to raise their voices of protest and translate their rights into the Constitutions of democratic States. The social transcendence of the present topic because the rights of women have always been violated in each stage of social development. In view of this abuse of women's rights, protection standards have been created at the international level. We find the Inter-American Convention to Prevent, Punish and Eradicate Violence against Women, "Convention of Belem Do Pará, Brazil," held on June 9, 1994. In Ecuador on December 11, 1995, the Law against Violence against Women and the Family is published in the Official Registry in defense of the physical, psychological and sexual integrity of women and other members of the family, sanctioning only these abuses as contraventions of domestic violence; The Comprehensive Organic Law to Prevent and Eradicate Violence against Women, with its respective Regulations, in force since February 5, 2018, is in force. 6 In the case of crimes against the life of a woman, the repealed Penal Code sanctioned those responsible as a crime of murder or murder. With the creation of the Organic Comprehensive Criminal Code that came into force in August 2014, the crime of femicide is typified, recognizing a right and guarantee of gender of women, prohibiting discrimination and abuse of women against men who have always come taking advantage of their gender condition. Currently, women are occupying and representing very high positions in public administration and executive function, the paradigm that women could not overcome men is being erased, although in Middle Eastern countries they continue to discriminate against women. The laws of Latin America have incorporated into their regime the crime of femicide or femicide, to prevent impunity for deaths of women by imposing penalties of up to thirty-five years; including life sentences to those guilty of committing these crimes that threaten women's lives. Each State has established criminal policies to combat and eradicate violence and protect the lives of women. The development of theoretical contents and the results of the survey and interviews allowed to obtain criteria, clear and precise foundations, of well-known bibliography, which contributed to the verification of objectives, and the contrast of the hypothesis, allowing to present alternative solutions. The content of the thesis is the result of an arduous legal research immersed in the scientific, legal, social and methodological field, which addresses theories and knowledge obtained through techniques and methodology of legal and applied research.